Diferencias en el gasto alimentario según características socioeconómicas y de seguridad alimentaria y nutricional en hogares de Medellín (2017)
ABSTRACT: The proportion of food expenditure in the home with respect to total household expenditure is an inverse indicator to wellbeing. Objective: To analyze the differences in the proportion of food expenditure in Medellin households according to socioeconomic characteristics and food security classifications. Materials and Methods: A cross-sectional study in 3008 households in Medellin that participated in the 2015 Food and Nutrition Security Profile in Medellin. Food expenditure was analyzed according to food security, characteristics of the head of household, location of living space, socioeconomic strata, and places where purchases are made. The statistical tests chi-square, Spearman and ordinal logistic regression were applied. Results: Households classified as food-insecure presented with a higher proportion of food expenditure (p=0.000). An inverse relationship was found between the proportion of household expenditure and income and education level of the head of household (p=0.00). Also, a higher probability was found between high proportion of food expenditure and households of low socioeconomic status (p=0.00), and households located in rural areas. Households with a higher proportion of food expenditure are more likely to purchase foods at local stores and shops (p=0.00). Conclusion: There is a greater proportion of food expenditure in Medellin households of low socioeconomic status, located in rural areas, with low educational level of the head of household, and who make purchases in local stores.